Portugal : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2009)
This report describes Portugal's observance of Standards and Codes on the Financial Action Task Force Recommendations for Anti-Money Laundering and combating the financing of terrorism. The Portuguese legal framework for combating money laundering (ML) and terrorist financing is generally comprehensive. The ML offence is broad in scope and in accordance with the UN Vienna and Palermo Conventions. Statistics on prosecutions for money laundering and terrorist financing, as well as related confiscation data, are maintained by Portuguese authorities.